Control of a back‐to‐back converter as a power transfer system using synchronverter approach. Issue 9 (21st February 2018) - Oñate, Marcelo; Posada, Johnny; López, Jesus; Quintero, Jaime; Aredes, Mauricio
Abstract : This study presents an innovative approach where both sides of a back‐to‐back (BtB) system are controlled using the synchronverter approach, allowing to control the power transfer through the converters as it would be in a real motor–generator pair system. A novel way to transfer the DC voltage control loop in the BtB converter is proposed, letting to a softer and less noisy power transferring, as shown in simulation results. The modelling equations of the synchronverter and the traditional dq frame in a BtB converter are presented in this work. In addition, a comparison between these two control approaches using three different performance indexes is done, showing that the power transfer behaviour using the synchronverter approach is significantly improved. Finally, the ability of the BtB converter working as a power balancer system (PBS) to manage congestion between two distribution networks in a test bed case is tested. Results show that it is possible to obtain the PBS power quality benefits without the additional phase‐locked loop units and the decoupling process, necessary with the dq frame, resulting in a simpler controller design.